Impact of Agriculture Factor and Non-Agriculture Factor to Value of Food Production: Cast Study of Vietnam, Thailand, Indonesia and Philippines Period 2010-2019 - Firmansyah, Muhamad Ferdy; Pusparini, Dewi Pratiwi; Vivero, Arriane A.; Lababit, Neldren Grace (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Food production provides an overview of developing a country's agriculture resilience and food security. Several factors can affect food production. They can be divided into agriculture factors and non-agriculture factors. This research aims to find agricultural and non-agricultural factors affecting food production. We assume the food production with a used average value of food production. A quantitative approach using a panel data model approach using for this research. The data used is secondary data. The results are that the factors that can affect food production with a used average value of food production are dependent variables. In this research, we used independent variables as follows agriculture land are, agriculture value-added, employment in the agriculture sector, credit to agriculture, and control variable. Control variables used in this research are annual population, gross domestic product, and political stability. This research is based on Vietnam, Thailand, Indonesia, and the Philippines. We used data panel regression for estimating the model, the data period used is in the period 2010-2019. This study provides recommendations that in increasing the optimization of food production, it is necessary to plan for value-added, empower workers, suppress population growth, and political stability.